Edge Computing Application of Expressway Intelligent Transportation System Based on IoT Technology - Wang, Jianqiang; Shang, Peini (Computing and Informatics, 2024)
With the comprehensive arrival of the fifth generation mobile communication technology (5G) era, the Internet of Things (IoT) has developed rapidly and is widely used in various industries. As one of the modern transportation signs, highways play an irreplaceable role in social and economic development. The research on Intelligent Traffic Systems (ITS) on highways has always been a hot topic. With the continuous improvement of the highway network and the increasing mileage, the efficiency of the existing highway ITS in processing information and solving problems is relatively low. Introducing new technologies to achieve breakthroughs has become a top priority. Edge computing is widely used in the Internet of Things technology because of its low latency and high response speed. Based on the characteristics of edge computing technology, this paper conducted in-depth research on expressway ITS, and analyzed the specific functions of intelligent system through IoT technology and edge computing technology. Through analysis and experiment, it is concluded that in the experimental highway area, the ITS using edge computing technology has slightly improved compared with the traditional ITS in all aspects. The response speed of the monitoring system has increased by 4.9 %, the congestion rate has decreased by 11.27 %, the congestion duration has decreased by 37.3 %, and the accident rate has decreased by 7.63 %. The edge computing application of expressway ITS based on IoT technology has improved the safety and comfort of residents' travel. It not only improves the intelligence level of intelligent transportation systems, but also enhances the safety and comfort of residents' travel, meeting the travel needs of modern people.